Engineering–economic simulations of sustainable transport policies - Zachariadis, Theodoros (My University, 2007)
The paper describes an engineering–economic model of the transport sector in the European Union (EU). The model starts with a simulation of the economic behaviour of consumers and producers in order to calculate the modal split and allocate the vehicle stock into vintages. Then a technologyoriented algorithm calculates air pollutant and greenhouse gas (GHG) emissions. The paper describes briefly the methodological approach, but its main focus is the presentation of results from scenarios that attempt to simulate sustainable transport policies. A major conclusion is that individual measures cannot address sufficiently the sustainability concerns. Therefore, policies combining technical and fiscal measures would be most appropriate.